أثر التدريس باستخدام استراتيجية العصف الذهني في التحصيل وتنمية التفكير الرياضي لدى طلبة الصف الثالث الأساسي في مديرية قصبة الكرك - المعايطة، فداء عبدالله سليم; البشايرة، زيد علي عواد (جامعة القاهرة - كلية الدراسات العليا للتربية, 2024)
هدفت الدراسة الكشف عن أثر التدريس باستخدام استراتيجية العصف الذهني في التحصيل وتنمية التفكير الرياضي في مادة الرياضيات لدى طلبة الصف الثالث الأساسي في مديرية قصبة الكرك. تكونت أفراد الدراسة من (٥٤) طالبا وطالبة، توزعوا على مجموعتين: تجريبية درست وفق استراتيجية العصف الذهني، وضابطة درست وفق الطريقة الاعتيادية، وتمثلت أدوات الدراسة بدليل المعلمة في استخدام استراتيجية العصف الذهني التي تم إعدادها لأغراض هذه الدراسة في وحدتي (القسمة والكسور) تم التحقق من صدقها، واختبار التحصيل المكون من (۲۲) فقرة من نوع الاختيار من متعدد، واختبار التفكير الرياضي المكون من (۲۱) فقرة موزع على (٥) خمسة مهارات، تم التحقق من صدقهما وثباتهما. وقد أظهرت نتائج الدراسة وجود فروق دالة إحصائيا في الاختبار التحصيلي واختبار التفكير الرياضي لدى طلبة الصف الثالث الأساسي في مادة الرياضيات تعزى إلى طريقة التدريس، لصالح المجموعة التجريبية التي درست وفق استراتيجية العصف الذهني، وفي ضوء نتائج الدراسة تم اقتراح عدد من التوصيات، منها: تشجيع معلمات الرياضيات للصف الثالث الأساسي على استخدام استراتيجية العصف الذهني لما لها من أثر في التحصيل والتفكير الرياضي. This study aimed to identify the impact of teaching by using the strategy of brainstorming on achievement and development of mathematical thinking among the students of the third basic grade in Al-Karak directorate of education. The study sample consisted of (54) male and female students divided into two groups: the experimental group studied according to the strategy of brainstorming, and the control group that studied using the usual way. The study instruments were represented by the teacher's manual in using the strategy of brainstorming prepared for the purposes of this study in the modules of (division and fractions); its validity and reliability were verified, in addition to an achievement test that consisted of (22) multiple-choice items, and the test of mathematical thinking that consisted of (21) items distributed to 5 skills; their validity and reliability were verified. The results revealed that there are statistically significant differences in the achievement test and mathematical thinking skills among the students of the third basic grade in mathematics attributed to the method of teaching in favor of the experimental group that studied by using the strategy of brainstorming. In the light of the results, the study recommended the necessity of encouraging the teachers of the third basic grade to use the strategy of brainstorming due to its effect on achievement and mathematical thinking.
Keywords: استراتيجيات التدريس -- التعلم النشط -- التحصيل الدراسي -- طلبة المرحلة الأساسية -- الأردن